EIF Private Equity Mid-Market Survey 2023: Market sentiment, scale-up financing and human capital - Helmut Krämer-Eis; Annalisa Croce (European Investment Fund (EIF), 2023)
The EIF Private Equity Mid-Market Survey and the EIF Venture Capital Survey (the largest combined regular survey exercises among General Partners on a pan-European level) provide an opportunity to retrieve unique market insights. This publication is based on the results of the 2023 EIF Private Equity Mid-Market Survey, conducted by the EIF. The paper focuses on the market sentiment, as well as on issues related to scale-up financing and human capital. The study looks at the current situation, developments in the recent past and expectations for the future. It highlights substantial challenges, but also opportunities as perceived by survey participants. The main results are summarised and compared over time. The publication provides a valuable picture of the developments in the PE mid-market sector in 2023, as well as an outlook for the near future.
Keywords: 330